Systemic immune inflammation index and risk of stroke: a cross-sectional study of the National Health and Nutrition Examination Survey 2005–2018 - Xue, Hua; Zeng, Yuqi; Zou, Xinyang; Li, Yongkun (Frontiers in Neurology, 2024)
Background The incidence of stroke has increased globally, resulting in medical expenditures and social burdens over the past few decades. We aimed to explore the relationship between systemic immune inflammatory index (SII) and stroke using the National Health and Nutrition Examination Survey (NHANES) from 2005 to 2018. Methods Based on NHANES data, 902 stroke patients and 27,364 non-stroke patients were included in this study. SII was the independent variable and stroke was the dependent variable. Univariate and multivariate logistic regression analyses were used to explore the association between SII and stroke. Restricted cubic spline (RCS) method was used to test the nonlinear association between SII and stroke. Results Weighted logistic regression analysis showed a significant association between SII and stroke (OR: 1.985, 95% CI: 1.245–3.166, p = 0.004). The interaction test showed that the association between SII and stroke was not significant between strata (p > 0.05). A significant positive association between SII and stroke risk (OR >1, p < 0.05) was observed in the crude model, model I and model II. RCS analysis showed no nonlinear positive association between SII and stroke risk after adjusting for all confounders. Conclusion Our study determined that SII is associated with stroke risk. Given the inherent limitations of cross-sectional studies, further research is necessary to validate the causality of this association and to demystify the underlying mechanisms between inflammation and stroke.